Description of the female and redescription of the male of Sciopemyia sordellii (Shannon & Del Ponte, 1927), including the description of four new species of the genus Sciopemyia Barretto, 1962 (Diptera: Psychodidae: Phlebotominae) from Brazil - Chaves Júnior, Salvador P.; Shimabukuro, Paloma H. F.; Andrade, Andrey J. (Zootaxa, 2022)
Currently, there are 1,047 sand fly species described worldwide. Brazil holds the greatest species richness in the Americas. The genus Sciopemyia Barretto, 1962 consists of eight species with Sciopemyia sordellii as its type species. Described by Shannon & Del Ponte in 1927, based on a single male specimen from Argentina, it has two junior synonymies: Phlebotomus nordestinus Mangabeira, 1942 and Phlebotomus longicornutus Floch & Abonnenc, 1943. The female of Sc. sordellii was not formally described and, until now, the female described as Ph. longicornutus was considered the female of Sc. sordellii. Here, we provide the description of the female of Sc. sordellii as well as a detailed redescription of the male. In addition, after a taxonomic review of specimens previously identified as Sc. sordellii or “Sc. microps aff.” we propose the description of four new species. To obtain morphological and morphometrical data, specimens deposited in the “Coleção de Flebotomíneos” (FIOCRUZ/COLFLEB) and in the “Coleção de Flebotomíneos da Faculdade de Saúde Pública da Universidade de São Paulo” (LESP-Phlebotominae) were analyzed. Descriptions of Sciopemyia species and their synonymies were checked. A total of 318 specimens (145 females and 173 males) were examined and firstly grouped as morphospecies. Within the genus Sciopemyia, the closest species to Sc. sordellii is Sc. vattierae, whose males are separated by the size of flagellomere I, aedeagal ducts and epandrial lobe. Females, on the other hand, show differences in the spermathecae. The female of Sciopemyia apicalis sp. n. remains unknown; Wheareas, the male is morphologically closer to Sc. sordellii, and they differ on the arrangement of the spines of the gonostyle. Sciopemyia dantastorresi sp. n. and Sciopemyia shimabukuroae sp. n. are sister species, whose identification is only possible from male specimens, since no differences were found between females. The female of Sciopemyia birali sp. n. is similar to the females of Sc. microps and Sc. servulolimai but is distinguished from them by characters of the cibarium, palps, and individual spermathecal ducts. The male of Sciopemyia birali sp. n. remains unknown. Drawings and a dichotomous key for both sexes are provided.